Fatigue and anxiety mediate the effect of dyspnea on quality of life in amyotrophic lateral sclerosis. Issue 5 (3rd July 2022) - Young, Carolyn; Ealing, John; McDermott, Christopher; Williams, Tim; Al-Chalabi, Ammar; Majeed, Tahir; Roberts, Rhys; Mills, Roger; Tennant, Alan
Abstract: Introduction : Dyspnea (or breathlessness) due to progressive neuromuscular respiratory failure is common in amyotrophic lateral sclerosis (ALS). It is associated with anxiety, depression and reduced quality of life (QoL). For effective treatment, it is essential to understand the relationships between dyspnea, anxiety, depression and QoL. Methods : The UK Trajectories of Outcomes in Neurological Conditions-ALS study (TONiC-ALS) collected self-report measures from patients with ALS. Ordinal scales were transformed to interval-scaled estimates by the Rasch Measurement model. They were subsequently included in a series of path models where the focal relationships were dyspnea to QoL and dyspnea to depression. Results : Path analyses using 1022 participants showed that 60.5% of the variance of QoL was explained by fatigue, anxiety, dyspnea and disability. For depression, 54.1% of the variance was explained by a model of these factors. Dyspnea played an important but mostly indirect role in influencing QoL and depressive symptoms. Disability was dominated by all other factors in the model. Discussion : Dyspnea in ALS influences quality of life and depression largely through indirect effects, principally acting via anxiety and fatigue. Recognition of this is essential for clinicians to understand where to intervene for greatest benefit. Researchers must be aware that studies of the effect of dyspnea on QoL and depression require path models, measuring both direct and indirect effects, as the impact of dyspnea is likely to be significantly miscalculated if only direct effects are assessed.